1997
DOI: 10.1007/s002800050699
|View full text |Cite
|
Sign up to set email alerts
|

Radioenhancement by cisplatin with accelerated fractionated radiotherapy in a human tumour xenograft

Abstract: The aim of the present study was to investigate whether cisplatin would enhance the radioresponse of a human tumour xenograft when given in different schedules combined with accelerated fractionated radiation therapy. A human squamous carcinoma of the hypopharynx, FaDu, was grown in the thigh of athymic nude mice. Tumours were exposed to twice-daily 2-Gy fractions, applied 6 h apart over 2 weeks, 5 days a week, alone or combined with cisplatin given at maximally tolerated doses in three different schedules: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…The ER of 1.4-1.7 due to AMCA treatment in the L44 tumor indicates that the efficacy of radiation therapy is indeed potentiated by exposure of the tumor to AMCA. The ER observed for the L44 tumor is comparable with those found for several cytostatics such as gemcitabine [35,38,42], cisplatin [24], the camptothecin analogue RFS-2000 [2], 5-fluorouracil [33] and two taxane analogues [31]. Interestingly, in our study with the L44 tumor with AMCA no weight loss was observed in contrast to the studies with the cytostatics mentioned.…”
Section: Discussioncontrasting
confidence: 52%
“…The ER of 1.4-1.7 due to AMCA treatment in the L44 tumor indicates that the efficacy of radiation therapy is indeed potentiated by exposure of the tumor to AMCA. The ER observed for the L44 tumor is comparable with those found for several cytostatics such as gemcitabine [35,38,42], cisplatin [24], the camptothecin analogue RFS-2000 [2], 5-fluorouracil [33] and two taxane analogues [31]. Interestingly, in our study with the L44 tumor with AMCA no weight loss was observed in contrast to the studies with the cytostatics mentioned.…”
Section: Discussioncontrasting
confidence: 52%
“…Such an increase in cycling cells is expected to overcome the cell kill by chemotherapy, leading, therefore, to tumour repopulation. The poor tumour response to cisplatin administered alone agrees with the results obtained by Joschko et al [18] from human tumour xenografts. Tumour response after cisplatin was comparable to that seen in controls (untreated tumours).…”
Section: Tumour Repopulation Versus Drug Resistancesupporting
confidence: 90%
“…Mice with FaDu tumors were treated 3 times a week for 2 weeks with cetuximab (33mg/kg) [23][24], cisplatin (6mg/kg) [25], or their combination via intraperitoneal injection (6 tumors per group). Tumor volumes were measured once a day using calipers, and tumor volumes were calculated by (l*w 2 )/2, where l is the tumor length and w is the tumor width.…”
Section: Methodsmentioning
confidence: 99%